Molecular characterisation and protein expression of selected markers for agar yield and gel strength of Gracilaria species - Lim, Yi Yi (2018)
Gracilaria is a genus of economically important red algae that produce agar as their cell wall polysaccharides. The yield and quality of agar determine the commercial and industrial values of these seaweeds in the phycocolloid market. Traditional screening process of seaweed materials with good agar yield and gel quality is laborious, tedious, costly and requires huge amount of seaweed. The availability of molecular markers for agar yield and quality may offer a quick and accurate alternative for seaweed selection. The aim of this study was to develop protein markers that are related to agar yield and/or gel strength in Gracilaria species. The specific objectives were (1) to clone and express three candidate transcript markers identified from a previous study into Esherichia coli expression system, (2) to test and confirm the binding specificity of polyclonal antibodies to the recombinant proteins of candidate transcripts and seaweed proteins, and (3) to correlate the protein expression of candidate markers in different Gracilaria samples to their agar yield and gel strength. The three candidate markers chosen for this study were GcFBPA (putative fructose-bisphosphate aldolase), GcGALE (putative UDP-glucose 4-epimerase) and GcSMF (putative sulfatase-modifying factor 1) previously identified to be highly expressed in G. changii with good agar yield and gel quality. The open reading frame (ORF) of these three candidate markers that are 1,077, 1,038 and 1,251 bp, respectively, were successfully cloned into pET28(+) expression vector and transformed into Escherichia coli BL21 (DE3) pLysS strain. The conserved domains for GcFBPA (F_bP_aldolase, PF01116), GcGALE (Epimerase, PF01370; GDP_Man_Dehyd, PF16336; Polysacc_synt_2, PF02719) and GcSMF (FGE-sulfatase, PF03781) were identified from the Pfam database. The most abundant cis-acting regulatory elements present in the 1 kb promoter regions of the three candidate markers were those related to abiotic stress and hormone responsiveness. Recombinant proteins of GcFBPA and GcGALE were expressed as soluble proteins at both 30°C and 37°C, respectively, while recombinant GcSMF was expressed in the insoluble fraction at all temperatures tested (i.e. 20, 30 and 37°C) in auto-induction Luria Bertani medium for 16 hours. Polyclonal antibodies specific to these three candidate markers, were generated by immunizing rabbits with peptide antigen. Western blot showed that the custom made polyclonal antibodies were specific to GcFBPA, GcGALE and GcSMF recombinant proteins, however, only polyclonal antibodies against GcFBPA and GcGALE showed the expected protein band sizes when tested on Gracilaria samples. Trichloroacetic acid (TCA)-Phenol method was used for extraction of total protein samples from 20 different Gracilaria samples with different agar yield and gel strength. The protein expression of FBPA and GALE on these samples were evaluated using western blot and the protein intensities were quantified with ImageJ software. Statistical analysis showed that protein accumulation of GcFBPA and GcGALE was significantly correlated (P<0.01) with agar gel strength and agar yield, respectively. Western blot analysis of SMF could not be performed due to the absence of expected proteins when tested on Gracilaria samples. In conclusion, GcFBPA and GcGALE have potential to be developed as protein markers for selection of seaweed materials with higher agar yield or gel strength for marine aquaculture exploitation.